Analysis of Elderly Human-Robot Team Trust Models. (September 2015) - Ishak, Danielle; Nathan-Roberts, Dan
This proceeding evaluates three existing models of human-robot trust by means of a macroergonomic framework to find strengths, weaknesses, areas for improvement, and suggestions for future research. The models of human-robot trust that are evaluated are Transparency, Feedback and Emotion Theory. These current models from the literature are examined individually, and strengths and limitations are identified when viewed from a sociotechnical macroergonomic view. A case example of an existing home-health robot, Willow Garage's PR2 robot, was then used to demonstrate the overlaps and gaps between the models' ability to represent human-robot trust. The analysis found that all of the models had some limitations and relative advantages when compared to a holistic approach of building trust in a human robot relationship through a sociotechnical system. Implications, limitations, and further research are also discussed.